Cooperative Collision Avoidance at Intersections: Algorithms and Experiments - Hafner, Michael R.; Cunningham, Drew; Caminiti, Lorenzo; Del Vecchio, Domitilla (IEEE transactions on intelligent transportation systems, 2013)
In this paper, we leverage vehicle-to-vehicle (V2V) communication technology to implement computationally efficient decentralized algorithms for two-vehicle cooperative collision avoidance at intersections. Our algorithms employ formal control theoretic methods to guarantee a collision-free (safe) system, whereas overrides are only applied when necessary to prevent a crash. Model uncertainty and communication delays are explicitly accounted for by the model and by the state estimation algorithm. The main contribution of this work is to provide an experimental validation of our method on two instrumented vehicles engaged in an intersection collision avoidance scenario in a test track.